Vitamin D deficiency in newborns: a tropical paradox - Naomi Esthernita F. Dewanto; Theresia Santi; Zaneth Sugiri; Nancy Napitupulu; Juandy Jo (Indonesian Pediatric Society, 2026)
Background Previous studies have shown a 'tropical paradox' in Indonesia, where despite being a tropical country with abundant sunlight, a widespread vitamin D inadequacy is observed in various populations. This paradox extends to Indonesian children, who predominantly exhibit low vitamin D levels, yet research specifically investigating vitamin D status in the newborn remains notably limited. Objective To determine the prevalence of low level of vitamin D and elucidate its correlation with the conditions of newborns in Jakarta, Indonesia. Methods This retrospective study analyzed data from newborns undergoing assessment at Siloam Hospital Kebon Jeruk, Jakarta, from June 2022 to May 2024. We collected the following data: newborn’s vitamin D level, demographic and clinical characteristics, as well as available maternal data. Serum 25-hydroxyvitamin D [25(OH)D] levels between < 20, 20–29.9 and ≥ 30 ng/mL were classified as deficient, insufficient, and sufficient, respectively. Statistical analyses were used to compare baseline characteristics and outcomes based on vitamin D status. Results Of the 243 newborns studied, 70.4% were classified as vitamin D deficient, 22.2% as insufficient, and 7.4% as sufficient. Subjects’ median vitamin D level was 15.7 (range 1.2 – 57.1) ng/mL. No significant difference in vitamin D levels was observed between male and female newborns (p=0.190) and between newborns with birthweight < 2,500 and the ones with birth weight ≥2,500 grams (p=0.794). Vitamin D levels were not significantly different between healthy and sick newborns (p=0.537). Maternal vitamin D status was available for only a small proportion (15.6%) of mothers, highlighting the need for further investigation into maternal-newborn vitamin D status. Conclusion Although a high prevalence of newborn with vitamin D deficiency was observed in our study participants, no significant difference in vitamin D levels was observed between healthy and sick newborns. No correlation was observed between sex or birth weight, and vitamin D levels as well. Future inquiries should explore maternal vitamin D status in greater detail and assess the prolonged health consequences of hypovitaminosis D in newborns.